The Rain It Poured - Bakanova, Aygul (Kyrgyzstan, 2010)
A teenage woman, Begaim, lives in a small village in Kyrgizstan, close to Lake Issyk-Kul. She got married recently, but her husband left shortly after the wedding and works as an illegal migrant worker in Russia. Begain is heavily pregnant, lives as a servant with her grandmother-in-law in the village and expects calls from his husband. She is being mocked by fellow women about her husband never turning back, because he allegedly found an other woman in Russia.
Donation from OSI-Budapest Arts and Culture Program.
Duration: 00:24:00
Keywords: Fiction films